1986
DOI: 10.1136/bmj.293.6561.1534
|View full text |Cite
|
Sign up to set email alerts
|

Role of vagal neuropathy in the hyponatraemia of alcoholic cirrhosis.

Abstract: minimal bactericidal concentration of amoxycillin was 27-4 tmol/l (10-0 pg/ml) but the minimal inhibitory concentration was only 0 07 ,umol/l (0-025 [&g/ml); the failed prophylaxis against this relatively tolerant pathogen was ascribed to persistent exposure to largeinocula. Fromour dataeven ninehours after takingamoxycillin serum concentrations exceeding the minimal inhibitory-concentration (0-07 pmol/l) were likely but bactericidal concentrations pmol/l) would not have occurred. Clearly, even if amoxycillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Cirrhosis, both alcoholic and nonalcoholic, has been reported to be associated with autonomic neuropathy, as well as other hemodynamic and circulatory disturbances [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It has also been reported that the prevalence of autonomic neuropathy is proportional to the severity of cirrhosis [3,8,9], and its presence is an indicator of poor prognosis in patients with both early and advanced liver cirrhosis [3,12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Cirrhosis, both alcoholic and nonalcoholic, has been reported to be associated with autonomic neuropathy, as well as other hemodynamic and circulatory disturbances [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It has also been reported that the prevalence of autonomic neuropathy is proportional to the severity of cirrhosis [3,8,9], and its presence is an indicator of poor prognosis in patients with both early and advanced liver cirrhosis [3,12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Chronotropic incompetence is the failure of the heart rate to respond to physiological and pharmacological stimuli. Sympathetic activation by various means, such as Valsalva maneuver, ice-cold skin stimulation, mental stress, tilting, and isometric and isotonic physical exercise, does not evoke an adequate acceleration of heart rate despite a higher than normal increase in plasma norepinephrine concentrations [23,24]. Such a defect is exhibited by both alcoholic and nonalcoholic patients and is proportional to the severity of cirrhosis.…”
Section: Electrophysiological Abnormalitiesmentioning
confidence: 99%
“…First, the autonomic nervous system plays a central role in maintaining cardiovascular homeostasis, and an impaired autonomic function is expected to lead to hemodynamic abnormalities. Second, AD is commonly detected in patients with cirrhosis, [9][10][11][12][13]16,[18][19][20][21]35 and its prevalence increases in parallel with the severity of liver disease, 9,10 as does the hyperdynamic circulatory syndrome. 36 Moreover, the presence of both abnormalities heralds an adverse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It has also been reported that the severity of AD is proportional to the severity of cirrhosis, 9,10 and its presence is an indicator of poor prognosis in patients with both early and advanced liver disease. [16][17][18] Finally, AD is associated with an impairment of free water generation and hyponatremia, 19,20 and is likely involved in the pathogenesis of prolonged electrocardiographic Q-T interval, 21 a common finding in advanced cirrhosis with an adverse prognostic significance. 22 Based on the previous discussion, we hypothesized that AD is involved in the pathophysiology of hyperdynamic circulation of advanced cirrhosis.…”
mentioning
confidence: 99%